Controlling petty corruption in public administrations of developing countries through digitalization: An opportunity theory informed study of Ghana customs. Issue 2 (15th March 2021) - Addo, Atta
Abstract: Despite myriad anti-corruption interventions, including digitalization-based efforts, petty corruption in public administrations of developing countries persists, undermining socioeconomic development. Extant research that links corruption to social and economic conditions has yielded inconclusive findings on whether digitalization can reduce corruption. Informed by opportunity theory from the field of criminology, which suggests that opportunities – rather than motives or systemic factors – beget crimes, we explore an alternative approach in this study: how digitalization could reduce the opportunities for petty corruption. We draw on a case study of the 30-year digitalization effort at Ghana's customs administration based on fieldwork, including 91 in-depth interviews with current and former customs officials, importers, clearing agents, banks, regulators, and other stakeholders. Our findings suggest that information technology enables corruption control over time by reducing corruption opportunities through sociotechnical reconfiguration of work practices and organizational arrangements.